CSC798: Web Architecture / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2020)
This course introduces the notion of Web architecture and its application. It emphasizes the classification of Web architectures from the general web application to the web service-oriented computing. The techniques and methods to design and analyze the architecture are also studied. It also includes Web 2.0 as a modern Web architecture. The scalability of the Web architecture is also emphasized for dealing with a complex Web environment.